Higher cardiorespiratory and muscular fitness in males could not be attributed to physical activity, sports practice or sedentary behavior in young people - Diogo Henrique Constantino Coledam; Philippe Fanelli Ferraiol; Arli Ramos de Oliveira (Revista Brasileira de Cineantropometria e Desempenho Humano, 2018)
The purpose of the present study was to analyze if the association between sex with cardiorespiratory and muscular fitness is independent of physical activity, sports practice and sedentary behavior in young people. A cross-sectional study involving 729 participants aged 10 to 17 years. Physical activity, sports practice and sedentary behavior were assessed through a questionnaire. Cardiorespiratory fitness was measured using 20m shuttle run test and were analyzed: VO2max, number of laps and health-related criteria. Muscular fitness was assessed with 90o push-up test and number of repetition and health-related criteria was analyzed. Multiple linear regression was used to estimate β coeficients and Poisson regression estimated prevalence ratios (PR). Male sex was associated to higher cardiorespiratory fitness (VO2max β = 9.04 to 9.77, Laps PR=1.67 to 1.80, health-related criteria PR=2.03 to 2.09) and the same occurred with muscular fitness (repetitions PR=2.81 to 3.01, health-related criteria PR=1.91 to 2.09). Similarly, the stratification of the sample according to physical activity, sports practice and sedentary behavior did not change the associations between sex with cardiorespiratory (VO2max β=8.07 to 10.00, Laps PR=1.49 to 1.85, health-related criteria PR=1.64 to 2.27) and muscular fitness (repetitions PR=2.24 to 3.22, health-related criteria PR=1.76 to 2.06). These data suggest that higher cardiorespiratory and muscular fitness in males could not be attributed to physical activity, sports practice or sedentary behavior in young people.